Focus cardiac ultrasound: the European Association of Cardiovascular Imaging viewpoint. (1st September 2014) - Neskovic, Aleksandar N.; Edvardsen, Thor; Galderisi, Maurizio; Garbi, Madalina; Gullace, Giuseppe; Jurcut, Ruxandra; Dalen, Havard; Hagendorff, Andreas; Lancellotti, Patrizio; ,; Popescu, Bogdan A.; Sicari, Rosa; et al.
Abstract: The concept of point-of-care, problem-oriented focus cardiac ultrasound examination (FoCUS) is increasingly applied in the settings of medical emergencies, including cardiac diseases. The European Association of Cardiovascular Imaging (EACVI) recognizes that cardiologists are not the only medical professionals dealing with cardiovascular emergencies. In reality, emergency cardiac diagnostics and treatment are also carried out by a wide range of specialists. For the benefit of the patients, the EACVI encourages any medical professional, sufficiently trained to obtain valuable information from FoCUS, to use it in emergency settings. These medical professionals need to have the necessary knowledge to understand the obtained information entirely, and to use it correctly, thoughtfully and with care. In this document, the EACVI underlines major differences between echocardiography and FoCUS, and underscores the need for specific education and training in order to fully utilize advantages and minimize drawbacks of this type of cardiac ultrasound examination in the critically ill patients.